Calculation of Greenhouse Gas Emissions and Carbon Stock (Case Study of Small Services Company X) - Sonya Okta Deviro; Irfan Fadhlillah Nugraha; Gunawan Ismail; Sahrul Sidik (Universitas Ibn Khaldun Bogor, 2024)
Company X possesses a high carbon potential, yielding 18,117.24 Tons/Ha or 1.81 Tons/m² annually. Despite generating 788.10 Tons/CO2 /year, there is an excess emission of 13,886.27 Tons/CO2 . The solution involves sustainable practices such as energy efficiency, wise waste management, green technology, and sustainability in the supply chain. Employee education and involvement are crucial in reducing emissions by promoting sustainable lifestyles. Transparency through carbon footprint measurement and reporting will build public trust. The integration of these measures is expected to actively aid Company X in reducing carbon emissions and contributing to global climate change mitigation.